Diagnostic accuracy of ultrasonography with laparoscopy for assessment of benign adnexal masses - Sarbhai, Vinita; Yadav, Medha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Adnexal masses are one of the most common pathologies among women of all age groups. Objective of this study was to assess efficacy of ultrasonography in diagnosing adnexal pathology, rule out malignancy and its comparison with laparoscopy and pathology results. Methods: A total 32 women with benign adnexal mass were evaluated by clinical examination, ultrasonography and laparoscopy. Findings of ultrasound were compared with laparoscopy and histopathology reports and diagnostic accuracy was calculated. Results: Sensitivity of USG in diagnosing simple ovarian cyst is 20% and specificity is 88.9% while laparoscopy has sensitivity of 100% and specificity of 94.4%. USG versus laparoscopy has sensitivity of 50% versus 100% and specificity of 94.1% versus 100% in diagnosing endometrioma. Sensitivity of USG in diagnosing dermoid cyst is 66.7% and specificity is 95% while laparoscopy has both sensitivity and specificity of 100%. USG and laparoscopy, both have 100% sensitivity and specificity in diagnosing ectopic pregnancy, para-ovarian cyst and TO abscess. Benign serous cystadenoma is a histopathological diagnosis and is missed by both laparoscopy and ultrasonography. Conclusions: Ultrasonography should be the primary imaging modality used to identify and characterize adnexal masses, as it is readily available, and noninvasive.